Computational Studies on Isolated Compounds of Sclerochloa dura; their Efficacy towards Carbonic Anhydrase Inhibition and Anti-cancer Drug Targets - Ali, Majid; Zaidi, Asma; Farooq, Umar; Sarwar, Rizwana; Bukhari, Syed M. (Letters in Drug Design & Discovery, 2021)
Background: In the previous study, we reported the isolation of six compounds from Sclerochloa dura and their in-vitro anti-inflammatory potential by their ability to inhibit phospholipase A2 (PLA2). The objective of current study is to inspect the effect of these compounds on other expected targets. Methods: For this purpose, various targets and percentage activities are predicted through CoFFer (QSAR) web service. All six compounds under investigation represented 99-100% activity towards carbonic anhydrases (CAs) and 90-100% activity towards anti-cancer drug targets. As active site of most of the carbonic anhydrase isozymes is conserved, we selected cytosolic human carbonic anhydrase II (hCA II) for docking studies which is ubiquitous and involved in various human disorders such as glaucoma, pulmonary edema and epilepsy. Anticancer drug targets include vascular endothelial growth factor receptor 2 (VEGFR2), glucocorticoid receptor (GR) and tyrosine protein kinase (c- SRC). Interaction of these compounds with hCA II (PDB ID:3P4V) and anti-cancer drug targets such as VEGFR2 (ID:3WZD), GR (ID:5G5W) and c-SRC (ID:2SRC), were analyzed through molecular docking studies using MOE (Molecular Operating Environment). Results: The findings suggested that most of these compounds represent excellent binding affinity with hCA II by making interaction with zinc-coordinated water molecule through sulfonic acid group or hydroxyl group present in the compounds. Similarly, five out of six compounds represented excellent interaction with VEGFR2. Interactions with GR indicated that compounds 2, 3, and 6 bind effectively as compared to their co-crystallized ligands. However, among these, the excellent binding affinity with c-SRC was demonstrated by compounds 3 and 6. Conclusion: This study revealed that all these compounds exhibited excellent interaction with the active site of hCA II, however in the light of previously reported data and due to membrane barrier, only compound 1 (due to long hydrophobic tail) and compound 4 (due to absence of bulky carbohydrate groups), can only penetrate inside the cytosol. Compounds 2, 3, 4, and 6 containing bulky carbohydrate moieties cannot penetrate inside the cell, therefore, they might have selective nature towards membrane-bounded tumor-associated hCA IX. This anti-tumor property of compounds was also proved by docking studies with VEGFR2, GR and c-SRC. Therefore, these compounds may have synergistic effects against inflammation and cancer. The ADMET studies show that compounds have moderate absorption and permeability along with slight toxicity.
Keywords: Molecular docking study